The Rogun Dam project: evolution from conflict to cooperation between Tajikistan and Uzbekistan - Salewicz, Kazimierz A.; Nakayama, Mikiyasu (Frontiers in Water, 2025)
The Rogun Dam project, designed to be the world’s tallest dam, represents a remarkable case of transboundary water conflict transformation in Central Asia. This study examines how relations between Tajikistan and Uzbekistan evolved from near-military confrontation to emerging cooperation over this contentious hydropower project. Initially conceived during the Soviet era as an internal infrastructure development, the dam became a flashpoint for regional tensions following the USSR’s collapse in 1991, with downstream Uzbekistan strongly opposing its construction. Through qualitative case study methodology, we analyze how domestic political dynamics—particularly leadership change in Uzbekistan in 2016—fundamentally altered bilateral relations and regional hydropolitics. Our research reveals that while technical assessments by international organizations provided necessary factual foundations, the decisive factor in conflict transformation was the shift in political leadership that prioritized economic integration and mutual benefits over zero-sum competition. This study contributes to transboundary water management literature by demonstrating that internal political transformations can be as significant as international diplomatic frameworks in resolving seemingly intractable water disputes. The Rogun case offers valuable insights for addressing similar conflicts globally, highlighting how leadership-driven diplomatic shifts can transform water conflicts into opportunities for regional cooperation. Through qualitative case study methodology incorporating analysis of publicly available various sorts of documents, we traced the evolution of bilateral relations over three decades while examining the interplay between domestic political transitions and international water diplomacy frameworks. Semi-structured content analysis of documents was supplemented with contextual examination of regional economic and geopolitical factors influencing stakeholder positions.